ChemInform Abstract: P‐Toluenesulfonic Acid‐Mediated Three‐Component Reaction "On‐Water" Protocol for the Synthesis of Novel Thiadiazolo[2, 3‐b]quinazolin‐6(7H)‐ones. Issue 22 (12th May 2016) - Wadhwa, Preeti; Kaur, Tanpreet; Singh, Neetu; Singh, Udai P.; Sharma, Anuj
Abstract: The scalable microwave‐induced operationally simple multi‐component reaction between 5‐aryl‐1, 3, 4‐thiadiazol‐2‐amines, cyclohexane‐1, 3‐diones and aromatic aldehydes, aliphatic aldehydes or formaldehyde proceeds with high atom economy and delivers multi‐annulated products in high yields.